Band alignment in ZrSiO4/ZnO heterojunctions. (March 2016) - Hays, David C.; Gila, B.P.; Pearton, S.J.; Kim, Byung-Jae; Ren, F.
Abstract: We have measured the band offsets of sputtered ZrSiO4 on bulk ZnO wafers using X-Ray Photoelectron Spectroscopy and obtained the bandgaps of these two materials using reflection electron energy loss spectroscopy. The valence band offset was determined to be −0.60 eV ± 0.04 eV for ZrSiO4 on ZnO, while the respective bandgaps were 3.22 eV for ZnO and 5.9 eV for ZrSiO4 . The conduction band offset for ZrSiO4 /ZnO was then determined to be 3.28 eV. The ZrSiO4 /ZnO system has a staggered, type II alignment. This means that while ZrSiO4 may be useful for surface passivation applications on ZnO, it is not suitable for thin film transistors where a positive valence band offset is needed. Highlights: We measured the valence band offsets for ZrSiO4 on single crystal ZnO. A value of −0.60 eV was determined from XPS measurements, with a staggered Type II alignment. The conduction band offset can then be derived as 3.28 eV. These values are compared with those of other dielectrics on ZnO.